2006
DOI: 10.1097/01.nmd.0000221177.51089.7d
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Management of Cardiovascular Risk Factors in Patients With Type 2 Diabetes and Serious Mental Illness

Abstract: Cardiovascular disease is the leading cause of death in Type 2 diabetes, which commonly occurs in patients with serious mental illnesses (SMIs). We determined the extent to which patients with diabetes and SMI, relative to diabetes patients without SMI, met American Diabetes Association goals for cholesterol and blood pressure, met criteria for the metabolic syndrome, and were prescribed medications known to reduce cardiovascular events. We found that less than half of diabetes patients, both with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 45 publications
1
83
1
2
Order By: Relevance
“…Consistent with this observation are findings of significantly elevated ten-year coronary heart disease risk in individuals with SMI , which is likely a consequence of this population's high rates of Type 2 diabetes (Dixon et al, 2000), metabolic syndrome (Kreyenbuhl et al, 2006;McEvoy et al, 2005), and other cardiovascular risk factors, such as obesity (Daumit et al, 2003), physical inactivity , poor nutrition (McCreadie, 2003), and cigarette smoking (de Leon et al, 1995).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Consistent with this observation are findings of significantly elevated ten-year coronary heart disease risk in individuals with SMI , which is likely a consequence of this population's high rates of Type 2 diabetes (Dixon et al, 2000), metabolic syndrome (Kreyenbuhl et al, 2006;McEvoy et al, 2005), and other cardiovascular risk factors, such as obesity (Daumit et al, 2003), physical inactivity , poor nutrition (McCreadie, 2003), and cigarette smoking (de Leon et al, 1995).…”
Section: Introductionmentioning
confidence: 78%
“…This under-appreciation of risk may contribute to the high rates of cardiovascular morbidity and mortality and contrasts with some recent progress in achieving relatively adequate glycemic control in these patients (Dixon et al, 2004;Krein et al, 2006;Weiss et al, 2006). Previous reports have demonstrated that few persons with SMI and diabetes are achieving ADA recommended goals for cholesterol (Frayne et al, 2005;Kreyenbuhl et al, 2006;Weiss et al, 2006) or blood pressure (Kreyenbuhl et al, 2006;Weiss et al, 2006), which corresponds with reports of low rates of screening for cardiovascular risk factors, particularly for hyperlipidemia (Frayne et al, 2005;Goldberg et al, 2007;Krein et al, 2006). Further, previous crosssectional studies suggest that statins and ACE-inhibitors/ARBs are used infrequently in patients with SMI and diabetes (Kreyenbuhl et al, 2006;Weiss et al, 2006) who may reap particular benefits from these treatments.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…65 In another study of diabetes patients, those with SMI were 29 % less likely to be prescribed cholesterol-lowering statin medications, and 20 % less likely to be prescribed angiotensin-converting enzyme inhibitors or angiotensin receptor blocking agents than diabetes patients without SMI. 66 In a large VA study (N = 313,586) of people with diabetes, failure to meet diabetes performance measures was more common among people with mental illnesses, adjusting for various confounders, with AOR1. 61 Several studies speculate whether access to care, care coordination, provider biases, or patient-specific factors contribute to the poor diabetes care for this population.…”
Section: Management Of Type 2 Diabetes and Other Cardiovascular Diseamentioning
confidence: 99%
“…2 Mental illness significantly affects outcomes in patients with other chronic medical illnesses. [3][4][5][6][7][8][9][10] The concept of patient complexity, which encompasses the influences of multiple chronic diseases, demographic factors, and psychosocial issues on disease outcomes, 11,12 could prove helpful in understanding the interplay between co-occurring mental and medical illness. Although researchers have studied the deleterious effect of mental illness on medical illnesses, the experiences of providers and the clinical context in which they work to care for complex patients need further elucidation.…”
Section: Introductionmentioning
confidence: 99%